Tolerance, Growth, and Physiological Responses of the Juvenile Razor Clam (Sinonovacula constricta) to Environmental Ca2+ and Mg2+ Concentrations - Peng, Maoxiao; Li, Zhi; Liu, Xiaojun; Niu, Donghong; Lan, Tianyi; Ye, Bo; Dong, Zhiguo; Li, Jiale (Frontiers in Physiology, 2019)
To facilitate transplanting razor clam (Sinonovacula constricta) populations to inland saline-alkaline waters, we evaluated the tolerance of juvenile S. constricta (JSC) to Ca2+ and Mg2+ concentrations, and determined the effects of these ions on JSC growth and physiological parameters. After 30 days stress, the tolerable ranges of JSC to Ca2+ and Mg2+ were determined to be 0.19 mmol∙L-1-19.46 mmol∙L-1 and 0 mmol∙L-1-29.54 mmol∙L-1, respectively. The concentrations of Ca2+ (less than 0.65 mmol∙L-1 or more than 3.24 mmol∙L-1) and Mg2+ (less than 0.37 mmol∙L-1 or more than 14.17 mmol∙L-1) significantly inhibit JSC growth. Physiological enzyme activity no significant response when the concentrations range of Ca2+ and Mg2+ are 0.93 mmol∙L-1 - 6.49 mmol∙L-1 and 0.37 mmol∙L-1 - 14.77 mmol∙L-1, respectively. For transplantation practice, these data indicate that only high concentrations of Ca2+ (3.24-6.825mmol∙L-1) and Mg2+ (14.77-33.69mmol∙L-1) in target inland saline-alkaline water had significantly impact on growth and physiological response. In addition, present study suggests that the increase in Ca2+ and Mg2+ ion concentrations caused by ocean acidification will not affect the survival, growth and physiology of S. constricta. Current research suggests that S. constricta can adapt to extreme changes in the marine environment (Ca2+ and Mg2+) and may be an excellent candidate for inland saline-alkaline water transplantation practice.